2006
DOI: 10.1111/j.1420-9101.2006.01102.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the cost of resistance; experimental evolution in the filamentous fungus Aspergillus nidulans

Abstract: We have studied compensatory evolution in a fludioxonil resistant mutant of the filamentous fungus Aspergillus nidulans. In an evolution experiment lasting for 27 weeks (about 3000 cell cycles) 35 parallel strains of this mutant evolved in three different environmental conditions. Our results show a severe cost of resistance (56%) in the absence of fludioxonil and in all conditions the mutant strain was able to restore fitness without loss of the resistance. In several cases, the evolved strain reached a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
74
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 47 publications
0
74
0
Order By: Relevance
“…Thus, it is expected that, in the absence of drug, the proportion of the population represented by the drug-resistant subpopulation will decrease or be eliminated from the population. Alternatively, further evolution in the absence of drug can give rise to compensatory mutations, resulting in improved fitness of drug-resistant mutants (4,17,20,30). In fungal cells, where resistance is acquired via changes in the genome rather than via horizontal gene transfer, the situation appears to be more complex.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is expected that, in the absence of drug, the proportion of the population represented by the drug-resistant subpopulation will decrease or be eliminated from the population. Alternatively, further evolution in the absence of drug can give rise to compensatory mutations, resulting in improved fitness of drug-resistant mutants (4,17,20,30). In fungal cells, where resistance is acquired via changes in the genome rather than via horizontal gene transfer, the situation appears to be more complex.…”
Section: Discussionmentioning
confidence: 98%
“…Factors affecting the accumulation of compensatory mutations have been extensively studied in organisms with a rapid life cycle: bacteria, yeast and fungi. These studies identified factors including the rate of compensatory mutation (Poon and Chao, 2005;Gagneux et al, 2006;Schoustra et al, 2006), the environment (Bjö rkman et al, 2000;Reynolds, 2000) and the size of a population bottleneck (Levin et al, 2000;Maisnier-Patin et al, 2002). In organisms with longer generation time like weed species (often, only one generation per year), it is tempting to speculate that awaiting compensatory mutations might be less efficient than making use of the genetic diversity already present in the species.…”
Section: Discussionmentioning
confidence: 99%
“…Especially for echinocandins, clinically resistant strains were isolated shortly after their launch (11,12). The strong adaptation ability of fungi is well documented (13)(14)(15)(16), so it was not surprising to see antifungal drug resistance emerging quickly. Mutation hot spots in FKS1, which encodes beta-glucan synthase, were detected in some of the resistant strains but not in all (10)(11)(12).…”
mentioning
confidence: 99%
“…Aspergillus nidulans is used as a model for adaptation studies (13,14). Vegetative nuclei in a colony are mitotically derived from a single spore nucleus, so the only source of genetic variation in an A. nidulans colony is somatic mutation, which then is clonally propagated as a mycelial sector (14).…”
mentioning
confidence: 99%